Appropriateness of antibiotic prescriptions in ambulatory care in China: a nationwide descriptive database study. Issue 6 (June 2021) - Zhao, Houyu; Wei, Li; Li, Hui; Zhang, Mei; Cao, Bin; Bian, Jiaming; Zhan, Siyan
Summary: Background: Inappropriate antibiotic use greatly accelerates antimicrobial resistance. The appropriateness of antibiotic prescriptions is well evaluated, using big observational data, in some high-income countries, whereas the evidence of this appropriateness is scarce in China. We aimed to assess the appropriateness of antibiotic prescriptions in ambulatory care settings in China to inform future antimicrobial stewardship. Methods: We used data from the Beijing Data Center for Rational Use of Drugs, which was a national database designed for monitoring rationality of drug use. 139 hospitals that uploaded diagnosis and prescription information were included from 28 provincial-level regions of mainland China. Outpatient prescriptions were classified as appropriate, potentially appropriate, inappropriate, or not linked to any diagnosis for antibiotic use by following a published classification scheme. Antibiotic prescription rates for various diagnosis categories and proportions of inappropriate antibiotic prescriptions for different subgroups were estimated. Antibiotic prescribing patterns and proportions of individual antibiotics prescribed for different diagnosis categories were analysed and reported. Findings: Between Oct 1, 2014, and April 30, 2018, 18 848 864 (10·9%) of 172 704 117 outpatient visits ended with antibiotic prescriptions. For conditions for which antibiotic use was appropriate, potentially appropriate, and inappropriate, 42·2%, 30·6%, and 7·6% of visits were associated with antibiotic prescriptions, respectively. Of all 18 848 864 antibiotic prescriptions, 9 689 937 (51·4%) were inappropriate, 5 354 224 (28·4%) were potentially appropriate, 2 893 102 (15·3%) were appropriate, and 911 601 (4·8%) could not be linked to any diagnosis. A total of 23 266 494 individual antibiotics were prescribed, of which 18 620 086 (80·0%) were broad-spectrum and the top four most prescribed antibiotics were third-generation cephalosporins (5 056 058 [21·7%]), second-generation cephalosporins (3 823 410 [16·4%]), macrolides (3 554 348 [15·3%]), and fluoroquinolones (3 285 765 [14·1%]). Interpretation: Inappropriate antibiotic prescribing was highly prevalent nationwide in China. Over half of the antibiotic prescriptions were inappropriate in secondary-level and tertiary-level hospitals, suggesting an urgent need for outpatient antibiotic stewardship aimed at optimising antibiotic prescribing to achieve the goals set in China's 2016 national action plan to contain antimicrobial resistance. Funding: The National Natural Science Foundation of China.